FAMILY SUPPORT INCREASING THE DIET COMPLIANCE DIABETES MELLITUS PATIENTS IN INPATIENT WARD OF KEDIRI BAPTIST HOSPITAL WARD - Susanti, Meilina; Sulistyarini, Tri (Jurnal Penelitian STIKES Kediri, 2013)
Diabetes Mellitus is a disease that can not be cured. A balanced diet is one of way in management of Diabetes Mellitus. Constraint of Diabetes Mellitus diet handling is burnout of patients to follow dietary therapy and lack of family support, if there is no family support, Diabetes Mellitus patients will not obey implement diet, so uncontrolled Diabetes Mellitus and complications occur. The research objective to analyzes of family support improve patient compliance of Diabetes Mellitus diet. The design of the research was Cross-sectional with population Diabetes Mellitus patients in inpatient ward of Kediri Baptist Hospital who met the inclusion criteria. The sample of the research was 25 people with accidental sampling. The data of the research was analyzed using